Faktor Yang Memengaruhi Kejadian Stunting Pada Balita di Wilayah Kerja Puskesmas Tarempa Kecamatan Siantan Kabupaten Kepulauan Anambas Kepulauan Riau - Aulia Fitri; Nuraini Nuraini; Endang Maryanti (Jurnal Ventilator, 2024)
accordance with their age. While the stunting data at Tarempa Health Center is 58 cases. The purpose of the study was to analyze the factors that influence the incidence of stunting in toddlers in the Tarempa Health Center Working Area, Siantan District, Riau Islands. Anambas Islands Riau Islands. Design The research design used the Case Control method. The population in this study were all toddlers who experience stunting in the Tarempa Health Center Working Area, which is as many as 58 people. The sample in this study were toddlers who experienced stunting 58 people and 58 people were not stunted with the maching technique with a ratio of 1: 1. Analysis Data analysis used univariate analysis, bivariate with chi-square test and multivariate with logistic regression. The results of logistic regression research show that there is an influence of parenting patterns p = 0.017, exclusive breastfeeding history p = 0.000 and history of infectious diseases p = 0.005. While the dominant factor influencing the incidence of stunting in toddlers is the history of exclusive breastfeeding p = 0.003 <0.05, with Exp (B) = 11.041 and 95% CI = 3,610-33,768. The conclusion of this study is that there is an effect of parenting, exclusive breastfeeding history and history of infectious diseases, which does not affect knowledge, attitudes, feeding patterns and immunization status. The dominant factor, namely exclusive breastfeeding history, influences the incidence of stunting in toddlers in the Tarempa Health Center Working Area, Siantan District, Anambas Islands Regency, Riau Islands. It is suggested that the Tarempa Health Center can create interesting education for mothers, such as conducting workshops/ demonstrations on how to provide good and correct and nutritious food for their children, as well as how to process diverse and nutritious foods so that children get good nutritional intake.